Analysis of Existence and Uniqueness for Riesz-Caputo Fractional Differential Equation with State-Dependent Delay - P.Senthilkumar,; K.Sangeetha, (Utilitas Mathematica, 2025)
This study atmost the existence and uniqueness of solutions for Riesz-Caputo fractional differential equations with State dependent Delays. The goal is to set up enough conditions, for the extant and individuality of solutions, investigating the interaction between the State dependent delay and Riesz-Caputo fractional derivative. An illustrative example is provided to demonstrate the result.